Analisis Kinerja Pemerintah Desa Dalam Pengelolaan Alokasi Dana Desa Pada Desa Kesokoja Kecamatan Palue Kabupaten Sikka - Agustina Paji; Henrikus herdi; Yan Yanitza Salvanos (Student Research Journal, 2023)
This research aims to determine the performance of the village government in managing village fund allocation in Kesokoja Village, Palue District, Sikka Regency. The design of this research is descriptive qualitative with data collection techniques in the form of observation, documentation and interviews. The type of data in this study is a type of qualitative data with primary data sources and secondary data sources. Data analysis in this study was in the form of data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the performance of the village government in managing village fund allocation is quite good, seen from several indicators, namely responsiveness, responsiveness and accountability. However, there are two indicators that have not gone well, productivity and service quality. Therefore, the assessment of productivity and service quality in the Kesokoja Village government must be improved. The preparation of activity programs must prioritize the programs contained in village development planning meetings as well as the transparency of village government officials towards the community in their accountability for managing Village Fund Allocations.